The Effect of Problem Based Learning Models Using Macromedia Flash and Motivation against Student Learning Outcomes on Environmental Pollution Materials - Tiara Arwira Mahdalena; Retno Dwi Suyanti; Daulat Saragi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study aims to determine: 1) whether the learning outcomes of students taught with problem-based learning models using macromedia flash are better than students taught with direct learning models, 2) whether the learning outcomes of students who have high motivation are better than students who have low motivation,3)  is there an interaction between the two learning models with the level of motivation in influencing student learning outcomes. This research is a quasi experimental study. The population in this study were all grade VII students of MTs Lab. UINSU Medan Academic Year 2018/2019 which consists of three classes. Samples were selected by cluster random sampling of two classes. . The instrument used was a student learning motivation questionnaire and student learning outcomes test. Data obtained from the research instrument were then analyzed using two-way anova in the SPSS 14.0 for Windows program. The results showed that: Student learning outcomes taught by the problem-based learning model were better than students taught by the direct learning model (sig. = 0.027 <0.05), Student learning outcomes that were highly motivated were better than students who were motivated low (sig. = 0,000 <0.05), There is an interaction between the two learning models with the level of motivation in influencing student learning outcomes (sig. = 0.018 <0.05).